Measurement of natural radioactivity in Chahbahar – Sistan and Blouchestan in Iran - Seyyed Abbas Hosseini (Iranian South Medical Journal, 2014)
Background: Natural radioactivity exposes radiation so that it goes whole body through different ways and causes diseases leading to death, if it is more than standard amount by ICRP. The aim of this study was to measure the amount of radioactivity in the soil, water and air of Chabahar city in Sistan and Baluchestan province, Iran. Material and Methods: A few locations of city were chosen as a sampling station. The study of drinking water radioactivity was performed in Bandargah and city square. Soil’ radioactivity tested in Tiss village and Shillat. Radioactivity measurement of air was performed in the above-mention places. The radioactivity of drinking water and soil were measured by using a coaxial detector Germanium with high purity. Results: Average concentrations of Ra-228, Th-222 and K-40 in soil and Ra-228 in piping drinking water and in consumed plant were 450±34.5 Bq/Kg, 28.5±2.5 Bq/Kg, 24.3±2.6 Bq/Kg and <2 Bq/L, respectively. The overall results demonstrated low levels of radioactivity (<2 mBq/L), and less levels of K-40, Ra-228 and Th-232 in soil. The Ra-228 concentrations measured in piping and underground water were generally below the detection limit. As there was lower radioactivity in comparison with international standards, there was not probably any disease. Absorbed dose in air was 485.5±20 nanoGy/h and effective dose was 596±24.5, 5 µSv. Conclusion: It is found that there is a significant difference in average of 228Ra, 40K and 232Th in the area relative to some points in the world that may be because of organic matter and microbial biomass. Different factors effect on radioactivity of samples. This region shows the least ionizing radiation.